Why the tennis "serve clock" may be a waste of time. Issue 4 (26th July 2018) - Kovalchik, Stephanie
Abstract : At the US Open this year, tennis players will be faced with a serve clock, giving them 25 seconds to take their first shot. The clock is intended to speed up pace of play. However, analysis byStephanie Kovalchik suggests the timer will make little difference Abstract : At the US Open this year, tennis players will be faced with a serve clock, giving them 25 seconds to take their first shot. The clock is intended to speed up pace of play. However, analysis by Stephanie Kovalchik suggests the timer will make little difference